Czech Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
The analysis is structured around the standard taxonomy of transmission channels. A monetary tightening must limit banks' ability to supply loans by reducing bank reserves/bank credit. The direct interest rate channel is the strongest channel of the monetary policy transmission mechanism (MPTM), but the exchange rate channel is weak. The government has started addressing the institutional impediments constraining credit to domestic enterprises. Joining the European economic and monetary unit will strengthen the pass-through from policy rates to lending rates.